Influence of vortices on a progressive quasi-plane acoustic wave - Perelomova, A. (Archives of Acoustics, 2006)
The projecting of the quasi-plane flow into specific modes yields in a set of coupled equations accounting for all possible interactions of the basic types of motion. A particular case of interaction considers vortices affecting the character of sound propagation. The new dynamic equations describing the propagation of a progressive acoustic beam interacting with a vortex background are derived and discussed. Since two acoustic branches become separated, these equations include the first order derivative with respect to time. It is the main result of the present paper. Illustrations on the scattered acoustic pressure referring to the different types of vortex flow are presented.